Evaluación multitemporal del cambio de cobertura vegetal en el Área de Conservación Regional Vilacota Maure - Oscco Coa, Carlos Enrique (2025)
The purpose of this research was to determine the change in vegetation cover in the Vilacota Maure Regional Conservation Area (ACR Vilacota Maure) located in the high Andean area of ​​Tacna, using Landsat satellite images, during the period 1988 - 2018. The classification of Vegetation coverage of the study area was carried out based on the international Corine Land Cover classification system, with the identification of classes or categories of vegetation cover for the years 1988, 2003 and 2018, and estimation of the annual rate of change. The total surface area of ​​the Vilacota Maure Regional Conservation Area was 124,313 hectares, where 05 categories of vegetation cover were identified according to the Corine Land Cover classification for the ACR Vilacota Maure: Permanent herbaceous crops 42.70 hectares (0.03%), Dense low forest 3,026.66 hectares. (2.43%), Grassland 94,127.66 ha (75.72%), Shrubland 1,545.43 ha (1.24%), and Peatlands and wetlands 4,670.90 ha (3.76%); and 03 types of non-vegetative cover: Bare lands 16,418.93 ha (13.21%), Glaciers 2,766.63 (2.23%), and Lagoons, lakes and swamps 1,714.27 ha (1.38%). The area covered by vegetation in 1988 was 102,396.95 ha, while in 2018 it was 103,413.36 ha, with a slight increase of 1,016.41 ha. The average gain of vegetation cover in the ACR Vilacota Maure in the period 1988 - 2018 was 32.91 ha/year, with an annual rate of 0.03%.